2006
DOI: 10.1007/s00299-006-0246-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of soft rot resistant calla lily by expressing a ferredoxin-like protein gene (pflp) in transgenic plants

Abstract: An efficient protocol for the Agrobacterium tumefaciens-mediated transformation of calla lily (Zantedeschia elliottiana (W. Wats.) Engl. cultivar 'Florex Gold') is described. Shoot basal discs were co-cultivated with A. tumefaciens C58C1 carrying a plasmid containing neomycin phosphotransferase (nptII) and plant ferredoxin-like protein (pflp) genes. After Agrobacterium co-cultivation, the shoot basal discs were exposed to 100 mg l(-1) kanamycin for selection. Twenty-eight out of 260 discs (10.8%) were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Transgenic expression of PFLP from sweet pepper in calla lily resulted in more resistance to soft rot bacterial diseases. 769 The same transformation in tobacco, orchid, and rice plants enhanced their resistance to Xanthomonas oryzae pv. oryzae .…”
Section: Fe–s Redox Centers In Electron Transfer Processesmentioning
confidence: 99%
“…Transgenic expression of PFLP from sweet pepper in calla lily resulted in more resistance to soft rot bacterial diseases. 769 The same transformation in tobacco, orchid, and rice plants enhanced their resistance to Xanthomonas oryzae pv. oryzae .…”
Section: Fe–s Redox Centers In Electron Transfer Processesmentioning
confidence: 99%
“…Cefotaxime concentration used to inhibit Agrobacterium tumefaciens growth in this study was the same as reported in a previous study (Yip et al 2007). After 2 days of cocultivation, the discs were then transferred onto the regeneration medium (BI medium containing 500 mg/l cefotaxime) and incubated at 26 ± 2°C with a 16-h photoperiod (60 lmol m -2 s -2 ) under cool white fluorescent lamps for 3 weeks.…”
Section: Growth and Recovery Of The Transgenic Plantsmentioning
confidence: 91%
“…This peptide has been reported to enhance resistance against bacterial pathogens such as Xanthomonas oryzae pv oryzae in rice (Tang et al 2001); Erwinia carotovora subsp. carotovora in transgenic Oncidium orchid Liau et al 2003); tobacco (Huang et al 2006) and calla lily (Yip et al 2007); Pseudomonas spp. in tobacco (Lin et al 1997;Huang et al 2004) and Ralstonia solanacearum in tomato .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that commercial hybrids of calla lily could partly escape from P. carotovorum infection within numberable years and the transgenic calla lily with ferredoxin-like protein gene (pflp) was relatively resistant to P. carotovorum subsp. carotovorum (Yip et al 2007). However, few reports on the effective control of this serious plant disease were documented.…”
Section: Introductionmentioning
confidence: 97%
“…Bacterial soft rot caused by P. carotovorum subsp. carotovorum is a serious plant disease in calla lily, and responsible for considerable losses in the industry of this plant (Snijder et al 2004;Yip et al 2007). It was reported that commercial hybrids of calla lily could partly escape from P. carotovorum infection within numberable years and the transgenic calla lily with ferredoxin-like protein gene (pflp) was relatively resistant to P. carotovorum subsp.…”
Section: Introductionmentioning
confidence: 99%